Time-Delay Analysis of Wide Area Voltage Control Considering Smart Grid Contingences in Real-Time Environment - Musleh, A.; Muyeen, S.M.; Al-Durra, A.; Kamwa, I.; Masoum, Mohammad Sherkat; Islam, Syed (IEEE, 2018)
IEEE This paper addresses the time delay effects of the wide area monitoring and control systems (WAMCS) in smart power grids which may critically impact system stability. The main purpose is to conduct a detailed delay analysis of the WAMCS in case of grid contingences. This analysis is performed via an advanced WAMCS testbed where a wide area controller (WAC) for a flexible AC transmission system (FACTS) device is implemented. The real-time measurements for the WAC are collected using phasor measurements units (PMU). The testbed is resulted from an interface of four main segments known as the WAC, the actual FACTS device, the local area controller, and the power grid system along with the PMUs are simulated via real time digital simulator (RTDS). To mimic the real case scenario both hardware-in-the-loop (HIL) and software-in-the-loop (SIL) schemes are adopted in the experimental testbed, considering time delay effects. The results obtained clarify the effect of delay in WAMCS in case of smart grid contingences.